Adaptive NK Cell Therapy Modulated by Anti-PD-1 Antibody in Gastric Cancer Model - Abdolahi, Shahrokh; Ghazvinian, Zeinab; Muhammadnejad, Samad; Ahmadvand, Mohammad; Aghdaei, Hamid Asadzadeh; Ebrahimi-Barough, Somayeh; Ai, Jafar; Zali, Mohammad Reza; Verdi, Javad; Baghaei, Kaveh (Frontiers in Pharmacology, 2021)
Adoptive NK cell therapy has become a promising treatment in recent years but has limited efficacy as a monotherapy. The identification of immune checkpoint inhibitors (ICI) molecules has opened a new horizon of immunotherapy. Herein, we aimed to demonstrate the cytotoxic effects of a polytherapy consisting of ex vivo expanded IL-2-activated NK cells combined with human Anti-PD-1 antibody as an important checkpoint molecule in a xenograft gastric cancer mouse model. EBV-LCL cell used as a feeder to promote NK cell proliferation with a purity of 93.4 %. Mice (NOG, female, 6–8-week-old) with xenograft gastric tumor were treated with PBS, administrated ex vivo IL-2-activated NK cells, IL-2activated NK cell along with human Anti-PD-1 (Nivolumab), and pretreating of IL-2-activated NK cells by Anti-PD-1 antibody. The cytotoxicity of ex vivo expanded NK cells against MKN-45 cells was assessed by a lactate dehydrogenase (LDH) assay. Tumor volume was evaluated for morphometric properties, and tumor-infiltrating NK cells were assessed by immunohistochemistry (IHC) and quantified by flow cytometry. Pathologic responses were considered by H&E staining. Ex vivo LDH evaluation showed the cytotoxic potential of treated NK cells against gastric cancer cell line. We indicated that the adoptive transfer of ex vivo IL-2-activated NK cells combined with Anti-PD-1 resulted in tumor growth inhibition in a xenograft gastric cancer model. Mitotic count was significantly decreased (*P<0.05), and the tumor was associated with improved infiltration of NK cells in the NK-Anti-PD-1 pretreated group (*P<0.05). In conclusion, the combination approach consisting of activated NK cells and Anti-PD-1 therapy results in tumor growth inhibition, accompanied by tumor immune cell infiltration in the gastric tumor model.